Bacteriophage as an anti-biofilm agent against Pseudomonas aeruginosa from wound infection - Padma Shrestha; Sujit Tandukar; Manisha Shrestha; Sanjit Shrestha; Anup Subedee; Jivan Shakya; Reshma Tuladhar (PLoS ONE, 2025)
Pseudomonas aeruginosa, an opportunistic pathogen associated with wound infections, resists many commonly available antibiotics. Its ability to form biofilm provides an additional trait to evade antibiotics. Biofilm-associated infections are difficult to treat, raising the need for alternative strategies. Thus, this research aimed to investigate the potential of bacteriophage to disrupt the biofilm produced by P. aeruginosa isolated from wound infections. Wound samples were collected aseptically, processed for the isolation of P. aeruginosa, and identified by standard microbiological methods. Antimicrobial susceptibility was determined by the Kirby-Bauer disc diffusion method. Bacteriophages were isolated using the double-layer agar method. Phenotypic assessment of biofilm formation by the isolates and its reduction by phages was conducted by the tissue culture plate assay. Out of 647 wound samples processed, 96 P. aeruginosa were isolated. Piperacillin/tazobactam was the most effective antibiotic, while doxycycline was the least effective. Among the total isolates, 86 (89.6%) were multidrug-resistant (MDR) and 69 (71.9%) were biofilm producers. Three different phages isolated from sewage demonstrated a high specificity to P. aeruginosa. Of these, phage vB_PaeP_PS2 lysed the highest number of isolates (22.9%), including 17 MDR and 21 biofilm-producing isolates. The biofilm reduction assay demonstrated that phage treatment significantly reduced biofilm formation, with vB_PaeP_PS2 achieving a 58% reduction after 6 h of treatment. In conclusion, this study highlights the high prevalence of biofilm-producing MDR P. aeruginosa in wound infections and, for the first time in Nepal, demonstrates the potential of locally isolated phages to lyse biofilm-forming MDR isolates and disrupt their biofilms.